MENGOPTIMALKAN PENDUDUK USIA PRODUKTIF SEBAGAI AKTOR UTAMA DALAM PEMBANGUNAN NASIONAL - Purba, Adyanto Armando; Tampubolon, Agustin Mahardika; Gaol, Rista Y. Lumban; Siregar, Ilman Ashari; Hidayat, Nasrullah (Jurnal Sosial Humaniora Sigli, 2024)
The productive age population is the population that has an age range of 15-65 years and is still able to work and produce something. Productive Age Population can be associated with a demographic phenomenon which is often referred to as a demographic bonus. The productive age population can be used to increase national development. National Development is an effort made to improve all aspects of the life of society, nation and state which can also be said as a process of developing the entire system of state administration in realizing national goals. However, if this potential is not utilized as well as possible, it will become a new problem for the country. Therefore, it is necessary to seek a solution to this challenge so as not to hinder the utilization of this potential. In optimizing this potential, there are several things that can be done, namely by developing human quality through education and training, expanding the labor market, managing population growth, and increasing the level of population health.Keywords : Productive age population, national development, window of opportunity.